Pratique et poétique du style : de l’utilité de l’étude stylistique pour l’édition - Caroline Blot (Perspectives Médiévales)
The study of selected examples from Prisonnier desconforté shows the significance of the literary heritage used by the poet. This can be seen in Ballade des proverbes, inspired by Villon, and through the assimilation of Psalms 102, both of which place the “I” of the Prisoner in the foreground. Meanwhile, the multiple morphological effects on prefixes, on the scale of an eighth or in the entire text, contribute to the author’s style. The modern publisher should render these marks left by the author in the author’s language as best as possible.